2021
DOI: 10.3390/info12020083
|View full text |Cite
|
Sign up to set email alerts
|

Device Discovery and Context Registration in Static Context Header Compression Networks

Abstract: Due to the limited bandwidth of Low-Power Wide-Area Networks (LPWAN), the application layer is currently often tied straight above the link layer, limiting the evolution of sensor networks distributed over a large area. Consequently, the highly efficient Static Context Header Compression (SCHC) standard was introduced, where devices can compress the IPv6 and upper layer protocols down to a single byte. This approach, however, assumes that every compression context is distributed before deployment, again limiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…One limitation of the SCHC protocol is that the context is static and must be distributed before deployment. Moons et al [ 10 ] introduce two context registration mechanisms for SCHC networks. The first mechanism extends the SCHC protocol with an adaptation layer, which is responsible for context registration.…”
Section: Related Workmentioning
confidence: 99%
“…One limitation of the SCHC protocol is that the context is static and must be distributed before deployment. Moons et al [ 10 ] introduce two context registration mechanisms for SCHC networks. The first mechanism extends the SCHC protocol with an adaptation layer, which is responsible for context registration.…”
Section: Related Workmentioning
confidence: 99%
“…Internet access was provided to LoRaWAN devices using SCHC in [143], where the authors also evaluated end-to-end security. In [144], authors presented a device discovery and context registration for SCHC and showed that SCHC can aignificantly reduce energy consumption.…”
Section: Related Workmentioning
confidence: 99%